Factors Influencing Job Satisfaction and Employee Loyalty for the Millennial Generation: Work Environment and Leadership Style - Tobing, Elida (Dinasti Publisher, 2022)
Literature review of the factors that influence job satisfaction and employee loyalty for the Millennial generation: work environment and leadership style are scientific articles that aim to build research hypotheses about the influence of variables to be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) Work Environment influences Job Satisfaction; 2) Leadership Style influences Job Satisfaction; 3) Work Environment influences Employee Loyalty; 4) Leadership Style influences Employee Loyalty; and 5) Job Satisfaction affects Employee Loyalty. Apart from these 2 exogenous variables that affect the endogenous variables Job Satisfaction and Employee Loyalty there are many other factors including the variables Salary/Wage, Rewards and Job Security.